Advanced solar tracking system with temperature control and real-time monitoring - Mahmuddin, Shohibul Syahmi; Nordin, Siti Aminah; Azli, Shakira Azeehan; Mohamad, Nurul Nadia (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The increasing demand for renewable energy has highlighted the inefficiencies of conventional static solar panels, which fail to maximize energy capture due to their inability to adapt to changing sunlight angles and environmental conditions. Addressing this challenge, this work presents the development of a Smart Solar Tracker system featuring wireless monitoring, temperature optimization, and real-time visualization utilizing the ESP32 microcontroller. The system integrates key components such as a humidity sensor, light-dependent resistor (LDR) sensor, servo motor, relay module, and LCD display, working in unison to optimize solar panel performance. The incorporation of a Wi-Fi module transforms the setup into an Internet of Things (IoT) device, enabling remote monitoring and control capabilities. The LDR sensor detects variations in light intensity, allowing precise adjustments of the solar panel’s position via the servo motor to maximize solar energy capture. Meanwhile, the temperature and humidity sensors provide critical environmental data to ensure efficient system operation. Leveraging the Wokwi simulation platform, the Arduino microcontroller processes sensor inputs and executes intelligent decision-making algorithms. These algorithms dynamically control the servo motor, relay module, and LCD display, adapting the system based on environmental conditions. The use of IoT technology enables enhanced accessibility through remote connectivity, offering real-time data visualization and system management. This scalable and versatile solution advances solar tracking by combining automation, wireless monitoring, and IoT integration, paving the way for improved energy efficiency and user accessibility.